Students’ Difficulties in Translating Narrative Text in the Third Grade of Smpn 5 Percut Sei Tuan - Evi Manullang; Nenni Triana Sinaga; Galina Sitinjak (Jurnal Mantik, 2022)
This research aims to describe the students' difficulties in translating narrative texts from Indonesia to English in the third grade of SMPN 5 Percut Sei Tuan. This research employed the qualitative method as a research design. The analytical method is the interactive model: data condensation, data display, and conclusion drawing/verification. The researcher collected data through steps by analyzing the student's paper when translating the narrative text into English. The result of this study showed that there are five types of difficulties in translating text, namely: not transmitted (11,11%), incomplete without hearing the message (12,96%), grammar mistakes (35,18%), vocabulary mistakes (31,48%), and addition (9,25%). Based on the test of the students' translation, this research showed the students' difficulties in translating narrative text. It was difficult for the students to translate a text, and some just used their minds or logic to translate it. The author suggests that the teacher focuses on teaching the students about translation and improving their vocabulary so that they can use good English when translating a text into English and another language.